Does Open Reduction in Intramedullary Nailing of Femur Shaft Fractures Adversely Affect the Outcome? A Retrospective Study - Syed Imran Ghouri; Abduljabbar Alhammoud; Mohammed Mubarak Alkhayarin (Advances in Orthopedics)
Aim. This study aims to assess the results of open versus closed reduction in intramedullary nailing for femoral fractures and whether it delays union, predisposes to nonunion, or increases the rate of infection. Materials and Methods. A retrospective review of all adult patients with isolated femoral shaft fractures treated by intramedullary nailing was done. The primary outcome is union rate, and the secondary outcomes are operation time and the infection rate. Results. 110 isolated femoral shaft fractures, with 73 (66.4%) in the closed reduction group and 37 (33.6%) in the open reduction group, 90.4% males and 9.6% females, and the average age was 32.6 years. RTA is the most common cause of these injuries followed by the fall from height. The delayed union rate was 20% (22/110) with no difference between the two groups, p value 0.480, and the nonunion rate was 5.5% (6/110), and no statistical difference was observed between the two groups. The operation time was shorter in the closed groups, and no difference in the time to union was observed between two groups. No infection was found in the two groups. Conclusions. There is no statistical difference between the healing rates in closed and open reduction in femoral shaft fractures. In cases where closed reduction is difficult, it is better to open reduce the fracture if closed reduction cannot be achieved in 15 minutes, especially in polytrauma.